The influence of preparation conditions on the electro-acoustic properties of the PZT-type piezoceramic sensors - DUDEK, J.; KOZIELSKI, L.; SUROWIAK, Z.; KUPRIYANOV, M. F. (Archives of Acoustics, 2000)
The possibilities of the application of the microstructure analysis, X-ray powder diffraction, and Raman scattering methods for the fast and reliable control of the quality of piezoelectric ceramic sensors at every stage of preparation are shown.